VIOLENCE-RELATED BEHAVIORS AMONG SCHOOL GOING ADOLESCENTS IN PENINSULAR MALAYSIA - Mat Reffien, Muhammad Alimin; Shamsul Azhar Shah; Lim KH (Malaysian Journal of Public Health Medicine, 2020)
Violence among adolescents is a significant public health issue. The focus was on school-going adolescents because of the life-long negative impact at an individual level both for the perpetrator and victim. Besides, it increases the costs to provide health, welfare, and criminal justice as well as decreases general productivity at the community level. The study aims to determine the prevalence of violence-related behavior, characteristics of both victims and perpetrators, in addition to inter and intrapersonal factors associated with violence-related behaviors. A study was carried out in 2013, which involved all upper secondary school students (aged 16 to 17 years). It was a part of the Malaysian Adolescent Health Risk Behavior (MyAHRB) study, which was conducted in 11 states in Peninsular Malaysia. Standardized, validated questionnaires were used for data collection. The prevalence of violence-related behaviors was 22.4%, and this was higher among male students as compared to females (29.1% vs. 16.3%). Multivariable analysis revealed that the odds of violence-related behaviour increased among males, Malay race, drug use, smoking, had exposure to sex, which sometimes and always felt lonely and had attempted suicide. Agreeable to ensure that their lifestyles do not transgress religious limit and belief was significantly protective. This study provides evidence for a targeted approach to combat violence-related behaviors among adolescents.